Karakteristik Manajemen Perubahan Pendidikan Islam Transformatif di MA Negeri 1 Nganjuk - Wathon, A; Maunah, Binti; Safi'i, Asrop (YASIN, 2025)
The rapid development of contemporary society requires educational institutions, including madrasah, to continuously adapt and innovate, thereby necessitating change management grounded in Islamic values and responsive to contemporary challenges. Although transformational leadership and change management have been widely studied, specific understanding of the characteristics of transformative Islamic education change management in the madrasah context remains limited. This study aimed to identify and analyze the key characteristics of transformative Islamic education change management implemented at MA Negeri 1 Nganjuk. Employing a qualitative approach with a phenomenological case study design, data were collected through in-depth interviews with the principal, teachers, staff, and the madrasah committee, participant observation, and document analysis. The findings show that the main characteristics of change management at MA Negeri 1 Nganjuk include a strong vision grounded in Islamic values, inspirational and development-oriented leadership by the principal, a collaborative and adaptive organizational culture, and curriculum and instructional innovation strategies that are responsive to contemporary demands. These findings contribute to the development of change management theory in the context of Islamic education and enrich the literature on best practices in madrasah settings. The study concludes that synergy between transformational leadership, a strong organizational culture, and continuous innovation is essential to realizing transformative Islamic education, and it offers practical implications for madrasah managers in designing effective and contextually relevant change strategies, as well as opening avenues for further research on the enabling and constraining factors in implementing transformative change across diverse Islamic educational institutions.